Religious Moderation in Aceh: A Strategy for Implementing Islam Washatiyah Values in Acehnese Society - Syibran Mulasi; Syaibatul Hamdi; Muhammad Riza (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article aims to look at the reality of religious moderation in Acehnese society, the challenges in implementing moderation values and the solutions in introducing religious moderation in Acehnese society. This study uses a qualitative approach with data collection conducted by interviewing academics at PTKIN Aceh and observing the development of moderation in society, namely by examining religious symptoms and conflicts in Aceh. The results of the study show that the practice of religious moderation had developed in Aceh long before the term moderation was echoed by the center, Acehnese people very easily accept anyone to live side by side even if they have different beliefs. The Acehnese with the principle of